Dysmenorrhea Awareness among Female Medical Students - Sumaira Fatima Sabir, Junaid Iqbal, Nimra Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dysmenorrhea is a problem of reproductive age, and effects quality of life, and is a common health concern among young females. Objective: To evaluate the prevalence of dysmenorrhea among female medical students and awareness of treatment options Study Design: Cross Sectional Study Place of Study: Azra Naheed Medical College and Allama Iqbal Medical College Duration: Two months from 01-01-2017 to 28 -02-2017 Methodology: An open ended questionnaire was given to 300 female medical students in two medical colleges, data on prevalence, severity of symptoms, treatment taken and limitations caused by dysmenorrhea obtained and analyzed. Results: Total 300 students were enrolled in study. Dysmenorrhea was reported in 276 students, out of which 148 students had bearable pain, 78 students had difficulty in their daily routine activities and 50 students were not able to perform daily activities. Home remedies and medicines were used by students for pain relief. The mean age of menarche was calculated as 12-13 years. Conclusion: Dysmenorrhea is a very common problem, and by increasing awareness to seek medical help in young girls will help them in performing their routine activities smoothly and thus decreasing the burden of problem.